Wireless Access Points Placement Analysis on WI-FI Signal Coverage with BAYESIAN Probability Method - Fawzan, Mahbub Puba; Sugiantoro, Bambang (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Wireless networks in a room are strongly influenced by interference. To overcome the interference and so that the performance from the wireless network is getting better, then optimization is done. There are several types of propagation that can interfere with the performance of wireless networks, which include the number of transmitters (access points), free space loss, Received Signal Strength (RSSI), coverage that can be served, measuring attenuation on barriers (concrete walls, soft partitions, doors, and floors).This research is an analytical study where the purpose of this study is to determine the position of access point a good in the Shari'ah Faculty Building and the Law using the method of Bayesian probability. The first stage of this research is to determine the distance of the signal reception to find out the strength of the signal with manual random sampling so that the data obtained varies. The second stage is to determine the position of the access point with a choice of several points so that the best position can be compared based on the plan of the Syari'ah Faculty and Law Building. The last step is calculating probability by the method of Bayesian probability.The results of this study are the position of the access point best on the 3rd floor, namely at position B with a probability value of 13 while on the 4th floor the position of access the point best in position A with a value of 10, position D with a value of 13 and position E with a value of 13. The most influential propagation in the Syari'ah Faculty Building and the Law is a concrete wall with a size of 60% reducing the magnitude of the signal emitted.(Abstract)